Deletion and elision in the spoken french of english-french bilinguals in the university of Ibadan, Nigeria (2020)
Deletion, which involves loss of segment involving vowels and consonants, is a common phonological process in language. Existing studies have examined deletion in several languages and dialects with less attention paid to the spoken French of English-French Bilinguals in the University of Ibadan, Nigeria. This article therefore examined deletion as a dominant feature in the spoken French of forty-four English-French Bilinguals in the University of Ibadan in Oyo State, South West of Nigeria with a view to establishing the dominance of deletion in the spoken French of the selected participants and how the English-French bilinguals approximate to the Standard French (SF). The data collection was through tape-recording of participants’ production of 30 sentences containing both French vowel and consonant sounds. The results revealed inappropriate deletion of vowel and consonant in the medial and final positions in their spoken French.